Penerapan Strategi Role Models dalam Pembelajaran Al-Qur'an dan Al-Hadits di SDIT Wahdatul Ummah - Wahyudi, Dedi; Oktaviana, Wiwin; Rahmiyati, Rahmiyati; Okta, Anggia Riskika (Tarbawiyah Jurnal Ilmiah Pendidikan, 2021)
In this study, it can be seen the phenomenon of children today who are reluctant to study the Qur'an or hadith. They show more interest in interesting applications found on their respective gadgets. The role of parents is also very much needed in the introduction of the Qur'an and hadith, so that they can know, learn, understand, and begin to apply them in everyday life. In addition to the education of both parents, children must also receive education from the teaching staff. The point is that children can get to know the outside world from other people, namely educators or teachers other than from the family. Education itself must be given to them so that they have a broad enough understanding so that their thinking is not narrow. Al-Qur'an and Al-Hadith should indeed be taught to them from an early age so that they can know the guidelines of human life. In addition, the lesson taken from these two instructions is that children can distinguish between right and wrong in being kind to their family and others, all of which have been recorded in the Qur'an and Al-Hadith. In Yosodadi village, there are many children who still want to learn the Qur'an or recite the Koran, but there is a lack of teaching staff so that educators at SDIT Wahdatul Ummah must maximize the teaching process. And the Messenger of Allah is the best example of an educator who must be an example for all mankind, including educators.